Article Review - Potensi Game Edukasi Dalam Upaya Pelestarian Batik Indonesia - Novan Edo Pratama (AKSA: Jurnal Desain Komunikasi Visual, 2019)
Educational game has potential in transferring knowledge. educational game makes it easy to deliver knowledge to students. one of the elements in the game, namely character, has a role in conveying the message. fun educational games make it so effective when it used in batik preservation. where batik is very diverse and it is not easy to learn the meaning and philosophy in it. the meaning and philosophy of batik in Indonesia deserves to be introduced to our next generation. with a learning process that is full of culture. This article discusses the potential of educational games in the learning process of preserving batik culture in Indonesia.